Holocaust consciousness and Cold War violence in Latin America - Tarica, Estelle (Albany : State University of New York Press, 2022)
Examines how community leaders, writers, and political activists facing state repression in Latin America have drawn on and debated the validity of Holocaust terms to describe human rights atrocities in their own countries.
Front Matter -- Contents -- Acknowledgments -- Introduction -- The Demands of the Times -- Holocaust Consciousness as Critical Consciousness in Post-dictatorship Argentina, 1995-2005 -- José Emilio Pacheco, Tununa Mercado, and Holocaust Testimony at the Mexico-Argentina Crossroads -- Demetrio Cojtí Cuxil's "Maya Holocaust" -- Holocaust Testimony and Maya Testimony between the U.S. and Guatemala -- Conclusion -- Notes -- Bibliography -- Index
Description based upon print version of record.
JSTOR
Keywords: Holocaust, Jewish (1939-1945) -- Foreign public opinion, Latin American; Politics and culture -- Latin America -- History -- 20th century; State-sponsored terrorism -- Latin America -- History -- 20th century; Genocide -- Latin America -- History -- 20th century; Latin America -- Politics and government -- 1948-1980.; Collective memory -- Argentina; Collective memory -- Guatemala; Collective memory -- Mexico; Politique et culture -- Amérique latine -- Histoire -- 20e siècle.; Terrorisme d'État -- Amérique latine -- Histoire -- 20e siècle.; Amérique latine -- Politique et gouvernement -- 1948-1980.; Mémoire collective -- Argentine; Mémoire collective -- Guatemala; Mémoire collective -- Mexique; LITERARY CRITICISM / Caribbean & Latin American; Collective memory; Genocide; Politics and culture; Politics and government; Public opinion, Latin American; State-sponsored terrorism; Argentina; Guatemala; Latin America; Mexico; 1900-1999; History; Literary criticism; Critiques littéraires.